Effect of Radiofrequency Waves of Mobile Phones on Distortion Product Otoacoustic Emissions - Nayak, Swetapadma; Aroor, Rajeshwary; Shastri, Usha; Goutham, M. K.; Sinha, Devika (Journal of Health and Allied Sciences NU, 2021)
Objective The prolonged exposure to electromagnetic fields of mobile phones can damage the cochlear hair cells, which can be detected by otoacoustic emission (OAE). To know the effect of mobile phones on hearing, the young volunteers were subjected to prolonged mobile phone usage and changes in OAE were recorded.Materials and Methods Twenty-eight volunteers with normal hearing were made to talk one full hour continuously on the mobile phone. Distortion product otoacoustic emission (DPOAE) was measured prior to the usage of mobile phones and immediately after the use (post-exposure 1) and 24 hours after the use (post-exposure 2). The values were compared.Results Out of the 28 volunteers, 20 were females and 8 were males. Twenty-one volunteers preferred the right ear while using mobile phones, 7 preferred the left ear. There was no statistically significant difference between the baseline DPOAE values and values of post-exposure 1 and 2 when only the preferred ear was taken into consideration. When the preferred ear was compared with nonpreferred ear, a statistically significant difference was found only in the low frequencies between the pre-exposure and post-exposure 1 values.Conclusion This study shows there was no significant correlation between OAE and prolonged mobile phone exposure when the preferred ear was not considered.
Keywords: mobile phone; otoacoustic emission; hearing loss